2022
DOI: 10.1002/adfm.202202068
|View full text |Cite
|
Sign up to set email alerts
|

Anodized Steel: The Most Promising Bifunctional Electrocatalyst for Alkaline Water Electrolysis in Industry

Abstract: Electrolysis of water, especially alkaline water electrolysis (AWE), is the most promising technology to produce hydrogen in industry. However, only 4% of the total hydrogen is produced in this way because the electrode materials are expensive, inefficient, or unstable. Here, it is reported that the large‐scale 3D printed martensitic steel (AerMet100) can be the bifunctional electrode for AWE with high catalytic performance, which may dramatically increase the green‐hydrogen percentage in the market and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…42 In contrast to the previously reported OER catalysts, it is found that the catalyst, with the introduction of Fe and Mo dopants, exhibits better OER catalytic performance. 43–48 The capacity of MoFe 0.5 O x Co(OH) 2− x regarding overpotentials is comparable to recently reported Earth-abundant OER catalysts with excellent performance (Table S2, ESI†). The catalytic kinetics of the presented catalysts were further evaluated by the Tafel slopes (Fig.…”
Section: Resultssupporting
confidence: 78%
“…42 In contrast to the previously reported OER catalysts, it is found that the catalyst, with the introduction of Fe and Mo dopants, exhibits better OER catalytic performance. 43–48 The capacity of MoFe 0.5 O x Co(OH) 2− x regarding overpotentials is comparable to recently reported Earth-abundant OER catalysts with excellent performance (Table S2, ESI†). The catalytic kinetics of the presented catalysts were further evaluated by the Tafel slopes (Fig.…”
Section: Resultssupporting
confidence: 78%
“…And the weak peaks belonging to CoOOH emerge from 1.3 V at around 504, 513, and 596 cm −1 , revealing a partial transformation from hydroxides to oxyhydroxides species. 55–57 Therefore, the new phases of hydroxides and oxyhydroxides are generated on the surface of CoIr@CN-0.20 during the OER process, in which the oxyhydroxide species could contribute to the superb catalytic performance. 55,57…”
Section: Resultsmentioning
confidence: 99%
“…55–57 Therefore, the new phases of hydroxides and oxyhydroxides are generated on the surface of CoIr@CN-0.20 during the OER process, in which the oxyhydroxide species could contribute to the superb catalytic performance. 55,57…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations